EFFECT OF SOME OF LIQUID MEDIA ON SOME GROWTH PARAMETERS AND VIABILITY OF BEAUVERIA BASSIANA (BALS.) VUILL. - Khamas, Muna; Diwan, Hussein; Kaddou, Ibrahim; Aboud, Hadi (Iraqi Journal of Science, 2024)
Eight liquid culture medium formulations were evaluated for their efficiency in enhancing some growth parameters (sporulation and biomass dry weight) of Beauveria bassiana after1, 2, 3 and 4days of incubation at 28±1C°. The formulations consist of saline solution (S), carbon source (8g/litre) and nitrogen source (0.33g/litre) as individually or as mixture of both sources with a C: N ratio of 24:1. These formulations were ; rice grains extract and casein (CRM), rice grains extract and yeast extract (YRM) , wheat seeds extract (CWM) and wheat seeds extract and yeast extract (YWM), rice grains extract (RM),yeast extract(YM), wheat seeds extract(WM), casein(CM).In other hand the spores viability were evaluated on selected medium CRM comparising with their viability on S,RM,CM after 1,2,3,4 and 8 days of incubation at 28±1C°. The results showed that the CRM was statistically in increasing the spore yield(133.3x105spore/ml) and dry weight (16mg/ml) after 4 days of incubation, while CWM and YM were less efficient for fungal sporulation (60.8x105spore/ml) and dry weight increment (5.54mg/ml), respectively at the same time of incubation. CRM was ideal for high percent viability (63%) compared with RM (42.9%), CM (41.5%) and S (20.1%).